The Experiment of Comparative Analysis of Lithuanian Manorial-Serf Economy and Hacienda Economic System of Latin America of the Second Half of the 18th – The Second Half of the 19th Centuries in the Context of Capitalist World System - Žiemelis, Darius (Lietuvos istorijos studijos, 2016)
The starting point of the article is considered to be the neo-Marxist Capitalist World System (CWS) concept by Immanuel Wallerstein, representative of comparative historical sociology. According to this concept, Lithuanian and Polish manorial-serf economies of the 16–18th centuries (exporting agricultural products to the core CWS countries) are classified as similar peripheral capitalist enterprises, like haciendas in Mexico and Brazil, and slavery coffee and cotton plantations in the US Southern states in the 18–19th centuries. This article is the first one in historiography where comparative analysis was carried out concerning Lithuanian manorial-serf economy and Latin America hacienda of the second half of the 18th – second half of the 19th century in the context of CWS – which proves the thesis that these economic systems belonged to typologically close economic type in the global division of labour. The second half of the 18th century–second half of the 19th century was the period of dominance and intensification of manorial-serf economy in Lithuania and predominance and intensification of hacienda economy in the countries of Latin America determined by the same industrial revolution factor. During the period under investigation, both Lithuanian manorial-serf economy and Latin American hacienda economy were found to be neither typically feudal nor to be peripheral capitalist enterprises (CWS concept in the strict sense), and manifested only peripheral capitalism features.
Keywords: Lithuanian manorial-serf economy; Latin American hacienda economy; second serdom; second slavery; peripheral capitalism; capitalist world system concept